GYNECOLOGICAL DISEASES AND THEIR MECHANISMS OF DEVELOPMENT (Web of Teachers: Inderscience Research, 2025)
Gynecological diseases encompass a wide range of conditions affecting the female reproductive system, including benign and malignant disorders, infections, and hormonal imbalances. These diseases can have significant implications for a woman's health, affecting fertility, menstrual function, and overall well-being. Understanding the underlying mechanisms of gynecological diseases is crucial for developing effective prevention, diagnostic, and treatment strategies. This article reviews common gynecological diseases such as endometriosis, polycystic ovary syndrome (PCOS), uterine fibroids, and gynecological cancers, focusing on their pathophysiological mechanisms, risk factors, and potential therapeutic approaches.